(untitled) (Revista Brasileira Multidisciplinar, 2009)
Gliobastomas are neoplasies that present themselves to be the most malignant among the astrocytic tumors. Their prognosis is ominous, with few years of survival. As we are dealing with such an aggressive illness, whose treatment is still so greatly limited, this study has had as objective to carry out a bibliographical revision to clarify the mechanisms of this illness and the advances in its treatment. One concludes that, despite the progress in the treatment of glioblastoma, it is still necessary to achieve more advances, by means of current promising researches, thus improving the quality of life of these patients.